Changing governance in the EU milk supply chain - Noortje Krol; Nico Polman; Jack Peerlings; Dimitre Nikolov (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
With the 2008 EU's CAP reform the governance of the EU's dairy sector changes. This paper focuses on governance structures between dairy farms and milk processors. To get insight in regional differences within the EU, a literature research and interviews are conducted in three case study areas, namely: the Netherlands, Bulgaria and France. Results show that in these countries both farmers and processors have incentives to form hybrid governance structures with a higher level of control compared to the current structures. Most dairy cooperatives have no additional advantage in managing milk quality and milk supply compared to investor owned firms. Chain integration could go a step further in Bulgaria compared to the Netherlands and France given the institutional environment that is not expected to guarantee milk quality and the focus on the export of milk.
Keywords: 330; Agricultural Markets; Marketing; Governance and Cooperatives